Imaging of Elbow Replacement Arthroplasty - Roth, Eira; Chew, Felix S. (Seminars in Musculoskeletal Radiology, 2015)
Elbow replacement arthroplasty has become a standard surgical treatment for a variety of diseases of the elbow. First popularized for the treatment of late-stage rheumatoid arthritis and other debilitating forms of joint disease, the current indications have expanded to include primary treatment of elbow trauma. The most commonly used total elbow replacements are linked semiconstrained chromium-molybdenum alloy or titanium alloy prostheses with polyethylene bearing surfaces. These are inserted after resection of the ulnotrochlear joint and typically cemented in place; the radial head is often sacrificed. Modular metal components or massive osteoarticular allografts may be used when there is extensive bone deficiency. Metal radial head replacements are increasing being used for primary fracture treatment and in posttraumatic elbow reconstructive surgery. Long-term outcomes for total elbow replacement are similar to those of other joints, with 10-year survivals of ∼90%. Complications specific to elbow implants include infection, aseptic loosening, prosthetic failure, and periprosthetic fracture.
Keywords: elbow arthroplasty; total elbow replacement; radial head replacement; radiocapitellar prosthetic arthroplasty